The Meaning of the Special Movement Silat Rajawali at the Tapak Suci Putera Muhammadiyah Sukabumi - Ainun Nisa Nurul Aulia; Yuliawan Kasmahidayat; Ace Iwan Suryawan (Universitas Pendidikan Indonesia, 2025)
The martial art of pencak silat is not only related to physical strength sports, but also contains artistic values and artistic meanings. This study aims to describe the meaning contained in the Rajawali Silat Technique at the Tapak Suci Putera Muhammadiyah Sukabumi School. This study is a deductive qualitative study supported by the theory of meaning and several other supporting theories. This study uses a descriptive analysis method with a qualitative approach. The object of this study is the Rajawali Silat Technique at the Tapak Suci Putera Muhammadiyah Sukabumi School, while the subjects of the study are Tapak Suci Warriors, Tapak Suci Cadres and also the Head of the Regional Leadership 186 Tapak Suci Sukabumi and Tapak Suci Sukabumi Students. Data collection was carried out through observation, in-depth interviews, and documentation studies. The results of this study are: (1) The Rajawali Silat Technique is a technique created by one of the Tapak Suci warriors, named Mohammad Anas (Tan Fung Wiek) to be used as a source of Tapak Suci knowledge; (2) The structure and technique of the Rajawali Silat Technique are taken from the Tapak Suci pencak silat science. The movements of the Rajawali Silat Technique are taken from the movements and habits of the Eagle bird which is brave, strong, tough but looks beautiful; (3) The meaning of the Rajawali Silat Technique as a whole is about the meaning of each movement taken from the habits of the Eagle bird, such as the habit of searching for prey and defending against threats. This Rajawali Silat Technique has a meaning in the special movements of the technique.